High Hole Mobility Inorganic Halide Perovskite Field‐Effect Transistors with Enhanced Phase Stability and Interfacial Defect Tolerance. (15th October 2021) - Lee, Yoon Jung; Han, Ji Su; Lee, Da Eun; Lee, Tae Hyung; Kim, Jae Young; Suh, Jun Min; Lee, Jung Hun; Im, In Hyuk; Kim, Seung Ju; Kwak, Kyung Ju; Jang, Ho Won
Abstract: So far, it has been difficult to fabricate thin‐film field‐effect transistors (TFTs) based on inorganic halide perovskites (IHPs) due to their phase‐instability and uncontrollable trap density. Here, the bottom‐gate bottom‐contact structured p‐type TFTs are presented using the optimized IHP in the active layer. The stable cubic‐CsPbI3 phase is successfully synthesized by doping bismuth iodide and reduced defect densities by adding potassium bromide. The IHP TFTs based on the tailored cubic‐CsPbI3 show high hole mobility of ≈ 10 cm 2 V −1 s −1, an on‐off current ratio of 10 3, and a low subthreshold swing voltage of 0.43 V dec −1 . In addition, the operational stability of the fabricated device is demonstrated through the bias stress test. This study suggests that one of the key factors for fabricating an ideal p‐type IHP transistor is managing charge transport properties in the IHP layer through defect engineering. Abstract : Fabricating phase‐stable and surface‐passivated inorganic halide perovskite (IHP) is demonstrated and applied to active layers of thin‐film field‐effect transistors (TFTs). Thanks to the successful fabrication, superior hole mobility of ≈10 cm 2 V −1 s −1, and operational stability are proved. These make IHPs a discriminated candidate for active layers of TFTs against the conventional organic‐inorganic hybrid halide perovskites in TFTs.